Chinese Consensus on Diagnosis and Assessment of Sleep Apnea Syndrome in Older Adults - Chinese Association of Geriatric Sleep Medicine, Chinese Geriatrics Society (Zhongguo quanke yixue, 2022)
It is a necessary trend to improve the quality of life of rapidly increasing number of older adults. Sleep disorders are significantly associated with the quality of life in older adults, among which sleep apnea syndrome (SAS) is second only to insomnia, which is an inducer of multiple diseases, and directly associated with many chronic diseases, such as cardiovascular and cerebrovascular diseases, Alzheimer's disease, metabolic abnormalities, respiratory diseases, even leads to sudden death. So SAS in older adults should be given great attention by the whole society. With this in mind, the Chinese Association of Geriatric Sleep Medicine, Chinese Geriatrics Society invited Chinese sleep medicine experts to develop a consensus on the classification, risk factors, clinical symptoms, diagnosis and assessment methods, diagnostic procedures as well as complications of SAS in older adults based on a review of relevant clinical studies, aiming to provide a reference for the standardization of SAS diagnosis and assessment in China.